Analysis of Employee Management in Improving The Performance of Shipping Service Companies - Agus Tamrin Reni (Universitas Negeri Padang, 2024)
This research investigates the influence of human resource management (HRM) and job satisfaction on business performance, using employee productivity as a mediating variable. The research used a quantitative survey targeting Shopee Xpress Sekupang Branch employees. A structured questionnaire was distributed to 116 respondents, selected through purposive sampling, to measure HRM, Job Satisfaction, Employee Productivity, and Business Performance. Data analysis was set utilizing SmartPLS to test the proposed hypotheses. The outcomes reveal that HRM and Job Satisfaction significantly favorably affect Employee Productivity and Business Performance, both directly and indirectly. Notably, Employee Productivity mediates the connection between HRM and Business Performance and between Job Satisfaction and Business Performance. These outcomes emphasize the critical role of effective employee management in enhancing organizational outcomes. The research highlights the importance of improving HR strategies to address operational inefficiencies and enhance service quality. Recommendations are provided for optimizing HR practices to foster a more productive and satisfied workforce, ultimately boosting business performance.